Family Support in Maintaining Dental and Oral Health with Dental Caries in Patients Suffering from Diabetes Mellitus Type 2 - Izzatun Nuriy Taufik; Siti Fitria Ulfah; Bambang Hadi Sugito; Imam Sarwo Edi (International Journal of Advanced Health Science and Technology, 2024)
Diabetes mellitus causes manifestations in the oral cavity which are usually called oral diabetes which include dental caries, dry mouth, gums that bleed easily (gingivitis), tartar, alveolar bone resorption, and periodontitis. Dental caries is the most common complication in people with diabetes mellitus type 2 with a high prevalence rate of up to 55%. It was found that on average patients suffering from diabetes mellitus type 2 at the Pakong Community Health Center, Pamekasan Regency experienced dental caries of 4.6, which is included in the high category. The problem of dental caries in patients suffering from diabetes mellitus type 2 is still high, and family support in efforts to maintain dental and oral health is still lacking. The aim of this research is to determine the relationship between family support in maintaining oral health and dental caries in patients suffering from diabetes mellitus type 2. This type of research is a cross-sectional correlation analytical research by means of examination and filling out questionnaires. The respondents in this study were 56 patients suffering from diabetes mellitus type 2 using the Slovin formula and using a purposive sampling technique. The data analysis technique uses the chi-square test. This research shows that there is a significant relationship between family support in maintaining oral health and dental caries in patients suffering from diabetes mellitus type 2 at the Pakong health center, Pamekasan district.